Necessity and random events in the evolution of the universe - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2009)
There are two extremities in contemporary discussions on the role of random events in the evolution of the Universe: one extremity consists in reducing the evolution to a blind game of random events, the other extremity in seeing everywhere traces of the 'intelligent design'. Both these doctrines are based on misunderstandings. It is argued that casual or random events are not a 'foreign body' in the network of physical laws, but rather its indispensable element without which the laws of physics would be ineffective.